Cobalt accumulation in horses following repeated administration of cobalt chloride. Issue 11 (16th August 2019) - Wenzel, RG; Major, D; Hesp, KF; Hall, E; Doble, P
Abstract : Objective: To monitor cobalt concentrations in urine, red blood cells and plasma after chronic parenteral administration of cobalt chloride evaluate these results against the current International Federation of Horseracing Authorities thresholds for detecting cobalt misuse. Design: Eight mares were randomly assigned to four treatment groups, with two mares in each group: Group 1 – control group, Group 2 – 25 milligrams cobalt intravenously as CoCl2 weekly, Group 3 – 50 milligrams cobalt intravenously as CoCl2 weekly, and Group 4 – 25 milligrams cobalt intravenously mid‐week and at the end of the week. Urine and blood samples were collected before each weekly administration so that trough levels were assessed. In the group receiving two doses per week, urine and blood were collected prior to the dose given at the end of each week. Samples were initially collected at time zero then weekly for 10 weeks. Three further collections of urine and blood were made at days 81, 106 and 127. Methods: Urine creatinine measurements to assess horse hydration status were performed by the Jaffe reaction method. Cobalt determinations in plasma, blood and urine were by inductively coupled plasma—mass spectrometry. Haematocrit concentrations, used to calculate red cell cobalt levels, were performed using a microhematocrit centrifuge. Statistical analyses were conducted in Genstat (v17, VSNi). Results: Marked cobalt accumulation was evident with increasing cobalt concentrations for all sample matrices in specimens collected immediately prior to cobalt administration. Correlation between the sample matrices improved when urine cobalt concentration was adjusted for creatinine level. Red cell cobalt levels remained elevated for at least 12 weeks after cessation of administration, consistent with the lifespan of the red cell. There was no significant change in haematocrit concentrations for the duration of the study. Conclusion: The current urine cobalt threshold was only effective at detecting acute cobalt exposure while the plasma cobalt threshold was able to consistently identify chronic high‐level cobalt exposure and potential cobalt misuse. The threshold values legislated for urine cobalt do not correlate with those set for plasma. The acute nature of urinary cobalt excretion provides a relatively small window through which cobalt administration is detected. Plasma and red cell cobalt concentrations can provide a clearer picture of potential cobalt misuse.